Effect of Colic Vein Ligature in Rats with Loperamide-Induced Constipation. (8th May 2012) - Neri, Flavia; Cavallari, Giuseppe; Tsivian, Matvey; Bianchi, Elisa; Aldini, Rita; Cevenini, Monica; Guidetti, Elena; Piras, Gian Luca; Pariali, Milena; Nardo, Bruno
Abstract : Introduction . Medical treatment in chronic constipation is not always successful. Surgery is indicated in unresponsive selected severe cases. This study presents the distal venous colic ligation in rat as a novel surgical approach. Materials and Methods . 16 rats (study group) were evaluated in 3 phases of 6 days each: A (normal conditions), B (loperamide-induced constipation), and C (colic vein legation) and compared with rats treated in phase C with PEG 4, 000 (control group). Blood biochemical and physiological parameters, daily fecal water content (FWC), and histological analysis were performed in all study phases. Results . No biochemical and physiological parameters changes were observed. FWC decreased in phase B and increased in phase C in both groups with a grow up to 2.3-fold in study group compared to control (P < 0.0001 ). Moreover, in study group, a high number of colonic goblet cells were detected (phase C versus phase B:P < 0.001 ) while no differences were registered in control. Conclusion . By ligature of the colic vein in constipated rats, an increase in FWC and goblet cells higher than in PEG treated rats was detected. The described surgical procedure appeared effective, simple, and safe; further studies in animal models, however, are necessary to assess its clinical applicability.